2011
DOI: 10.4067/s0717-95022011000200011
|View full text |Cite
|
Sign up to set email alerts
|

Variations of the Vocal Fold Epithelium in a Menopause Induced Model

Abstract: SUMMARY:During menopause, changes occur in the laryngeal structures that have implications for the voice. The purpose of this study was to determine the effect of induced menopause on the morphological parameters of the vocal fold mucosa in rats. Ten adult female Sprague-Dawley rats were used as samples and divided into two groups: 5 were surgically oophorectomized (OVX), and 5 underwent a surgical procedure similar to oophorectomy but without removal of the ovaries (SHAM). After 30 days surgery, the character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…In female rats, sex hormones are critical to homeostasis of the pre-menopausal vocal fold mucosal tissues [ 64 , 65 , 66 ]. Several studies have demonstrated that removal of the ovaries (elimination of ovarian hormones) results in the remodeling of the vocal fold mucosa including the following: decreased cellular layers of the epithelium, increased edema of the lamina propria, and decreased collagen I, hyaluronic acid, and elastin of the lamina propria [ 64 , 65 , 66 ]. Although ovariectomy procedures have demonstrated vocal fold mucosal remodeling, orchiectomy procedures in male rats have not resulted in significant remodeling [ 64 ].…”
Section: Review Of Sex Differencesmentioning
confidence: 99%
“…In female rats, sex hormones are critical to homeostasis of the pre-menopausal vocal fold mucosal tissues [ 64 , 65 , 66 ]. Several studies have demonstrated that removal of the ovaries (elimination of ovarian hormones) results in the remodeling of the vocal fold mucosa including the following: decreased cellular layers of the epithelium, increased edema of the lamina propria, and decreased collagen I, hyaluronic acid, and elastin of the lamina propria [ 64 , 65 , 66 ]. Although ovariectomy procedures have demonstrated vocal fold mucosal remodeling, orchiectomy procedures in male rats have not resulted in significant remodeling [ 64 ].…”
Section: Review Of Sex Differencesmentioning
confidence: 99%
“…Specially, the epithelium and lamina propria are negatively impacted by low estrogen levels following ovariectomy. Following ovariectomy, the lamina propria has increased inflammation and edema of the lamina propria, decreased hyaluronic acid, changes in collagen content, and decreased elastin content in the extracellular matrix, and the epithelium decreases in thickness and cellular layers 11,37,38 . Together these findings suggest that the TA muscles may not be affected by estrogen levels, but the overall vocal fold structure and consequently physiology is affected by estrogen levels.…”
Section: Discussionmentioning
confidence: 95%
“…Regarding the elderly women vocal quality, less roughness and stronger vocal loudness were observed after performing the sounded blowing exercise into a resonance tube ( Table 2). Roughness is present in elderly women, probably due to postmenopausal metabolic syndrome and hormonal changes that make the vocal fold thicker (21) , which may lead to changes in the mucosal wave vibration. After three minutes of performing sounded blowing exercise, there might occur an improvement in the mucosal wave vibration justified by the physiology of this exercise, that is considered to be a SOVTE (11,12) .…”
Section: Discussionmentioning
confidence: 99%